Apakah Penilaian Kinerja berdasarkan Sistem Badan Keuangan dan Asset Daerah Tepat dalam Mengukur Kinerja Pegawai? - Aristiyani, Danista (Universitas Darwan Ali, 2022)
This study aims to determine whether there is a difference between the performance appraisal based on the Regional Financial and Assets Agency system and the actual performance appraisal. This study uses paired sample t-test in its measurement method. The population in this study were all employees of the Regional Finance and Assets Agency (BKAD) of East Kotawaringin Regency with 83 people. In this study, the sample used was 60 people, this is because there are some people who do not meet the criteria as a reference for performance appraisal. Sampling using a purposive sampling technique. The results showed a significant difference between the performance appraisal based on the Regional Financial Agency and Assets system and the actual performance appraisal. Where the assessment based on the system is higher than the actual performance appraisal with a difference of -8.75000.